Determination of the Radon Concentration of Gas 222Rn Emitted From Sludge Samples Located in the Radioactive Waste Collection Warehouse in Khader Al-Maa South of Basra City – Iraq - Ali, Master A. (Journal of Petroleum Research and Studies, 2022)
Thirty-one samples of sludge were taken, stored at the natural radioactive waste collection site, NORM, in Khidir Al-Maa, south of Basra city, resulting from the operations of extracting and filtering crude oil in oil fields in Basra Oil Company, to determine gas concentrations Radon 222Rn and other radioisotopes in Sludge models. The rapid electronic technology was adopted through the RAD7 device, the active method, and the gamma analysis technique using HPGe High Purity Germanium Detectors to determine the specific activity of radioactive elements. The measurements for this study showed 98463±7031 Bq.m-3 in sample no. S10 a barrel of sludge was brought from the third Degassing Station plant in the northern Rumaila oil field and least concentrated is 8317±594 Bq.m-3 in sample no. S14 sludge belonging to the sixth Degassing Station / West Qurna-1, the study also revealed the presence of high concentrations of the specific effectiveness of radioactive isotopes (214Pb, 212Bi, 226Ra) and (212Pb, 212Bi, 228Ac) of the uranium-238 series and Thorium-232 series in a sludge form selected from a barrel returning to the third gas isolation plant - North Rumaila Oilfield and stockpile at the collection site, where the specific activity value of radium was 226 Ra 133851 Bq.k-1 of the uranium-238 series and for lead 212Pb 56432 Bq.k-1 of For uranium-238 series compared to their concentrations, 32 Bq.k-1 45 Bq.k-1 in a natural soil model. The effective dose to which on-site workers would be exposed in contact was calculated and found to be 196.92 Svh-1, a dose that exceeded the proposed 50 Sv. h-1 dose limits by the US EPA. The probability of developing cancer due to exposure to radon per million people was found and it was found to be a high value compared to the suggested value (170-230) per million people previously by ICRP.